Developing and identifying superior quality protein maize (QPM) cultivars - Magulama, Efren E. (USM R & D Journal, 2010)
This research project aimed to develop and identify QPM cultivars whose yield compared or were higher than normal maize. Eleven (11) sets of field trials consisting 191 QPM germplasm (125 experimental single-cross hybrids, 32 three-way crosses hybrids, 29 open-pollinated varieties, and 5 QPM populations) were evaluated for their field performance. Of the 191 experimental materials, 40 promising QPM materials from various variety types were selected based on their superiority over check varieties. The selected QPM germplasm included twenty eight (28) single crosses, seven (7) three-way cross hybrids, three (3) open-pollinated varieties, and two (2) populations. The superior QPM cultivars showed yield advantages ranging from 3 to 10% over OPVs, 1 to 28.0% for single cross hybrids, and 11 to 33% for three-way cross hybrids. The results demonstrated that QPM cultivars that can compete in yield with normal maize varieties.